2012
DOI: 10.1155/2012/719250
|View full text |Cite
|
Sign up to set email alerts
|

Different Apathy Profile in Behavioral Variant of Frontotemporal Dementia and Alzheimer's Disease: A Preliminary Investigation

Abstract: Apathy is one of the most common behavioral symptoms of dementia; it is one of the salient features of behavioral variant of frontotemporal dementia (bvFTD) but is also very frequent in Alzheimer's disease. This preliminary investigation was aimed at assessing the type of apathy-related symptoms in a population of bvFTD and AD subjects showing comparable apathy severity. Each patient underwent a comprehensive neuropsychological assessment; behavioral changes were investigated by the neuropsychiatric inventory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 40 publications
1
39
1
3
Order By: Relevance
“…Notably, each enrolled subject in the present study had significant neuropsychiatric disturbances, as assessed by NPI-Q and NPI-D scores. The high prevalence of neuropsychiatric symptoms in patients with bvFTD has been previously reported in other community-based studies (33,34). Patients with moderate-to-severe bvFTD had a higher NPI-Q total score than patients with mild bvFTD.…”
Section: Mild (N=20)supporting
confidence: 72%
“…Notably, each enrolled subject in the present study had significant neuropsychiatric disturbances, as assessed by NPI-Q and NPI-D scores. The high prevalence of neuropsychiatric symptoms in patients with bvFTD has been previously reported in other community-based studies (33,34). Patients with moderate-to-severe bvFTD had a higher NPI-Q total score than patients with mild bvFTD.…”
Section: Mild (N=20)supporting
confidence: 72%
“…2,3 Apathy has been described in association with focal lesions of the prefrontal cortex, 72 caudate nucleus, internal globus pallidus, and medial-dorsal thalamic nuclei, 73,74 and is also a common clinical feature reported in association with several neurodegenerative diseases, including Parkinson's disease, 75 Alzheimer's disease, frontotemporal dementia, 76 Huntington's disease, 77 and progressive supranuclear palsy. 78 Classically, apathy is the result of a disruption of emotional-aff ective mechanisms linked to the ventromedial prefrontal cortex, amygdala, and ventral striatum 3 (fi gure 3) and frequently reported in patients with the behavioural variant of frontotemporal dementia.…”
Section: Lesions and Neuroimagingmentioning
confidence: 99%
“…78 Classically, apathy is the result of a disruption of emotional-aff ective mechanisms linked to the ventromedial prefrontal cortex, amygdala, and ventral striatum 3 (fi gure 3) and frequently reported in patients with the behavioural variant of frontotemporal dementia. 76 In these patients, imaging studies 76 have shown that severity of apathy is related to orbitofrontal cortex abnormalities with grey matter atrophy in the dorsal anterior cingulate cortex and dorsolateral prefrontal cortex. In Alzheimer's disease, the degree of apathy severity has been linked to neurofi brillary tangles and volume loss in the medial prefrontal cortex, including the anterior cingulate cortex.…”
Section: Lesions and Neuroimagingmentioning
confidence: 99%
See 1 more Smart Citation
“…An example of this is that people with dementia who endorse more emotionally apathetic statements were more apathetic overall, and specifically showed more extreme and variable behavioral problems such as insensitivity and uncooperativeness [17]. A further study by Quaranta et al [18] using the NPI found there to be differing apathy characteristics between AD and frontotemporal dementia, where the latter were reported to more frequently endorse statements relating to a lack of initiation, decreased emotional output and diminished interest towards friends or family. However, the NPI is a tool designed to assess apathy amongst other behavioral impairments and does not examine apathy multidimensionally.…”
Section: Introductionmentioning
confidence: 98%